Anti-homer-3 Antibody Encephalitis in a 10-Year-Old Child: Case Report and Review of the Literature - Kuang, Zuying; Baizabal-Carvallo, José Fidel; Mofatteh, Mohammad; Xie, Sifen; Wang, Zhanhang; Chen, Yimin (Frontiers in Neurology, 2022)
Objective We present a rare case with anti-Homer-3 antibodies positive encephalitis in the youngest patient ever identified and reviewed the literature. Case Report A 10-year-old, Chinese boy came for evaluation of a 2-week history of cognitive impairment, irritability, dysarthria, and cautious gait. The neurological examination was consistent with the pan-cerebellar syndrome and encephalopathy. Cerebrospinal fluid (CSF) was inflammatory with increased leukocytes. Magnetic resonance imaging of the brain showed hyperintensities in both cerebellar hemispheres and vermis in Fluid-attenuated inversion recovery (FLAIR) and T2- weighted sequences. Infectious disorders were ruled out, but positivity for anti-Homer-3 antibodies was detected in the CSF, but not in the serum. Additionally, low titers of voltage-gated calcium channel (VGCC) antibodies were found in the serum. Treatment with intravenous (IV) corticosteroids did not provide meaningful clinical improvement; however, the patient achieved almost complete recovery (modified Ranking Scale score: 1) following IV immunoglobulin. Conclusion Anti-Homer-3 cerebellar ataxia with encephalopathy should be considered within the differential diagnosis of acute inflammatory cerebellar disease in children and it may coexist with VGCC antibodies.